Motivating Factors and Potential Deterrents to Blood Donation in High School Aged Blood Donors. (15th May 2016) - Finck, Rachel; Ziman, Alyssa; Hoffman, Matthew; Phan-Tang, Michelle; Yuan, Shan
Abstract : Background . To ensure an adequate supply of blood, collection centers must design campaigns that successfully recruit and maintain an active donor pool. Understanding factors that motivate and deter individuals from donating may help centers develop targeted recruitment campaigns. These factors among high school aged blood donors have not yet been fully investigated. Study Design and Methods . A voluntary, anonymous survey was administered to student donors at high school mobile blood drives. The survey instrument asked the students to rate several potential motivating factors in their importance in the decision to donate blood and several potential deterring factors in their future decision whether or not to donate blood again. The survey also asked the students to rate the desirability of several potential incentives. Results . Motivating factors that reflected prosocial, empathetic, and altruistic thoughts and beliefs were rated highly by students. Pain from phlebotomy was most commonly chosen as potential deterrent. Movie tickets and cookies/snacks at the drive were rated as the most attractive incentives. Conclusion . High school aged blood donors are similar to other donor groups in their expressed motives for donating blood. This group may be unique in the factors that deter them from donating and in their preferences for different incentives.